Computing bounds for the general sum-connectivity index of some graph operations - Akhter, S.; Farooq, R. (Algebra and Discrete Mathematics, 2020)
In this paper, we compute the bounds for general sum-connectivity index of several graph operations. These operations include corona product, cartesian product, strong product, composition, join, disjunction and symmetric difference of graphs. We apply the obtained results to find the bounds for the general sum-connectivity index of some graphs of general interest.